Investigation of crystal structure, electrical and dielectric response of Ga3+ substituted Sr–Ni Y-type hexaferrites as a suitable material for high frequency applications. Issue 12 (15th June 2023) - Arshad, Muhammad; Khan, Muhammad Azhar; Rasool, Raqiqa Tur; Arshad, Muhammad Imran; Albalawi, Hind; Abd-Rabboh, Hisham S.M.; Jacob, Jolly; Asghar, H.M. Noor ul Huda Khan
Abstract: Technology important ferrites ceramic Sr2 Ni2 Gax Fe12-x O22 (x = 0.00, 0.2, 0.4, 0.6, and 0.8) samples were produced using sol-gel auto combustion route. Structural, electrical, dielectric, and magnetic parameters were identified by substituting Ga 3+ at the Fe 3+ site. It was recognized that an increase of Ga 3+ content in (Sr2 Ni2 Gax Fe12-x O22 ) ceramic samples first decreased, then increased lattice parameters, and the density of samples was observed. This is because of the ionic radii and atomic weight of Ga 3+ and Fe 3+ cations. FTIR spectra show two characteristic absorption bands at 444-513 cm −1 caused by metal-oxygen vibrations. Due to the contribution of smaller grains of samples, the higher values of resistivity were observed, which vary from 3.78 × 10 10 (Ω cm) to 1.13 × 10 11 (Ω cm) by the substitution of Ga 3+ ions at the octahedral site. The activation energy was measured between 0.20 and 0.61 eV. The dielectric response of Ga 3+ substituted ferrite ceramic samples were studied in the 1 MHz-6 GHz frequency region. The Maxwell-Wagner bilayer model studied the effect of polarization with applied frequency on dielectric parameters. With the substitution of Ga 3+, minimal losses in the range 0.34–0.44, about 6 GHz, and a high Q-value of about 10, 000 were observed for each sample. In impedance spectroscopy analysis Cole-Cole plots confirm that the dielectric response is because of the influence of grain boundaries. The substitution of Ga 3+ enhances saturation magnetization (68.20–71.78 emu/g) while coercivity decreases (655.86–507.86 Oe). In the present finding, the low dielectric loss, moderate permittivity, high value of the Quality factor, and very high value of resistivity of about 1.13 × 10 11 that reduces the eddy current losses suggested that these materials are appropriate candidates for many high-frequency applications such as multilayer chip inductor, dielectric resonators, power applications, and microwave devices.